CONSUMER VALUATION MODEL IN THE CONTEXT OF RELATIONSHIP MARKETING - Rytel, Tomas (Ekonomika, 2009)
The aim of this paper is to present a theoretical model of the establishment of the value created to an enterprise by consumers, which would allow a complex measuring of the benefit of the exchange of relationships based on the totality of the features significant to the exchange of relationships. The problem of an increasing concern about with the form of the relationship exchange in the theoretical and practical context of marketing calls for the need to identify the specific features of the relationship exchange, which create the value of exchange with the consumer for the company. The concept of the relationship marketing dictates the measurement of the consumer valuation for the company not only in the financial and/or exchange duration variables, but also socio-emotional features of the exchange.It can be argued that the methods of the assesment of the e consumer valuation for the company and the models, which they create, are not adapted to the specific marketing concept and exclude the features of value-generating exchange for the company, which are characteristic of that concept. The article aims at the substantiattion of the hypothesis that the concept of the marketing of relationships dictates the measuring of the value created to an enterprise by the consumers not only by means of the financial variable and / or the variable of the lack of exchange, but also the socioemotional features of the exchange. The following methodology has been applied to confirm the hypothesis: proceeding from the system analysis of the research, the main features of the relationships characteristic of the exchange, which are interpreted as the significant variables for the measurement of the value of exchange have been marked; the totality of the features is used to create a new model of the establishment of the value created to an enterprise by consumers needed to measure the return from the relationships, describing the criteria of selection of the variables and the principles of their calculation.